Merajut Kembali Relasionallitas Masyarakat dan Pemerintah: Relevansi Politik Berasaskan Rekonsiliasi dan Kebenaran - Martin C. Barut; Pius Kanelmut; Krispianus W. Sarhe (Parahyangan Catholic University, 2021)
The center of the study of this paper is to explore and understand Armada Riyanto’s ideas about reconciliation and truth. The ongoing political and security dynamics generate new and rich awareness and meaning in the pursuit of peace. The methodology used in this paper is ‘phenomenology’, that is, everyday phenomena become the main source of philosophy. By looking at the political reality from marginal notes, from phenomenological experience, this research comes to the finding that the political concept based on reconciliation and truth is a relevant political program to seek peace. Reconciliation cannot be carried out without revealing the truth and a truth will have a deep meaning in the act of reconciliation. The government and society have a responsibility to cultivate the virtue of peace. The synergy between the government and the community determines the progress of the life of the nation and state.